(Cambridge IGCSE) First language english coursebook (fifth edition) - Cox, Marian (Cambridge University Press Cambridge, 2018)
Fully updated, flexible resources taking an active-learning approach that encourages students to aim higher in the 0500, 0524 and 0990 syllabuses.